2017
DOI: 10.1039/c7em00423k
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional vapor intrusion modeling approach that combines wind and stack effects on indoor, atmospheric, and subsurface domains

Abstract: Vapor intrusion exposure risks are difficult to characterize due to the role of atmospheric, building and subsurface processes. This study presents a three-dimensional VI model that extends the common subsurface fate and transport equations to incorporate wind and stack effects on indoor air pressure, building air exchange rate (AER) and indoor contaminant concentration to improve VI exposure risk estimates. The model incorporates three modeling programs: 1) COMSOL Multiphysics to model subsurface fate and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…The dominant effect can be determined by the balance in leakage area between ceiling, walls, flue and floor (Song et al 2014). Recent three‐dimensional modeling efforts have also shown that indoor concentrations vary in complex ways with wind speed, direction and the location of major openings in the building envelope (Shirazi and Pennell 2017; Shirazi et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The dominant effect can be determined by the balance in leakage area between ceiling, walls, flue and floor (Song et al 2014). Recent three‐dimensional modeling efforts have also shown that indoor concentrations vary in complex ways with wind speed, direction and the location of major openings in the building envelope (Shirazi and Pennell 2017; Shirazi et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This evidence could be understood considering CSM of CVI where wind speed and direction is only one component of VI driving forces and the number of other features along the pathway affecting indoor concentrations, including for example, details of the building condition and behavior as well as other VI driving forces discussed previously. The evidence for wind as a unitary indicator of VI concentrations is complex in that localized building‐specific winds and their effects can be influenced by topography, vegetation, building design and condition, orientation to the wind (Shirazi & Pennell, ; U.S. EPA, ), and, possibly, fluctuation of winds (DeVaull, ; Luo, ; Luo, Dahlen, Johnson, Peargin, & Creamer, ; U.S. EPA, ).…”
Section: Summary: Current Findings On Meteorological and Climatic Itsmentioning
confidence: 99%
“…Furthermore, buildings do not have a significant capacity to “store” or delay static pressure changes (that would be analogous to heat capacity), but soils do. DPs are influenced by many factors other than changes in static pressure, such as temperature differences and winds that are generated by meteorological processes at a great distance away from the building (U.S. EPA 2012b; Shirazi and Pennell 2017).…”
Section: Resultsmentioning
confidence: 99%